Pemberdayaan UMKM Sabuk Kulit di Dukuh Tengah Melalui Digital Marketing - Toriq Ardian Maulana Maskanith; Khafidhoh Khafidhoh (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Micro, Small, and Medium Enterprises (UMKM) play an important role in the Indonesian economy but often face challenges in marketing, especially in the rapidly developing digital era. This research focuses on empowering Leather Belt MSMEs in Dukuh Tengah, Nambangrejo Village, through digital marketing as a solution to increase product visibility and competitiveness. It aims to improve the skills of MSME owners in utilizing technology and digital platforms such as social media and e-commerce. This research uses qualitative data collection techniques; the author uses observation, interview, and documentation study techniques. This research shows that participants become more independent in managing digital marketing, more innovative in promotions, and able to reach a wider market. This empowerment helps MSMEs adapt to modern market demands and improve the sustainability of their businesses.